IMPROVING READING SKILL THROUGH CONTENT LANGUAGE INTEGRATED LEARNING (CLIL) APPROACH TO THE SEVENTH GRADE STUDENTS AT SMP NEGERI SELANGIT - Nadia fitria; Dwwi Syafitri; Episiasi (CV Grasta Glory, 2026)
This research investigates the effectiveness of the Content and Language Integrated Learning (CLIL) approach in enhancing the reading skills of seventh-grade students at SMP Negeri Selangit. Addressing the need for innovative instructional methods, the study utilized a pre-experimental design involving a single-group pre-test and post-test framework. A sample of 27 students was selected through cluster random sampling to participate in the intervention focusing on descriptive texts. The results demonstrated a substantial academic gain, with the average score rising from a pre-test mean of 49.44 to a post-test mean of 69.44. Statistical validation via a paired t-test yielded a t-obtained value of 7.22, significantly surpassing the t-table critical value of 1.705. These findings confirm that the CLIL approach—which merges subject content with language acquisition is highly effective in improving student outcomes. Consequently, CLIL is recommended as a robust pedagogical strategy for educators seeking to boost reading proficiency and contextual engagement in secondary education.